Republic of San Marino : 2020 Article IV Consultation-Press Release and Staff Report. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2020)
This 2020 Article IV Consultation discusses that San Marino is now facing very significant challenges owing to the recent coronavirus disease 2019 (COVID-19) outbreak, which has taken a heavy toll on local population and businesses. The staff report reflects discussions with the Sammarinese authorities in January 2020 and is based on the information available as of January 31, 2020. It focuses on San Marino's near- and medium-term challenges and policy priorities and was prepared before COVID-19 became a global pandemic and resulted in unprecedented strains in global trade, commodity, and financial markets. It, therefore, does not reflect the implications of these developments and related policy priorities. The outbreak has greatly amplified uncertainty and downside risks around the outlook. Staff is closely monitoring the situation and will continue to work on assessing its impact and the related policy response in San Marino and globally. With no credible measures to restore banking system health and in the face of a continued weak external environment, economic growth is projected to remain subdued in the coming years. Slow progress in repairing the banking system and failure to restore fiscal sustainability are the key and material risks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet